Articular Findings on Chest Computed Tomography: An Algorithmic Approach for Radiologists. Issue 6 (1st November 2022) - Mansoori, Bahar; Kosaraju, Vijaya; Yoon, James; Chalian, Hamid; Shomal Zadeh, Firoozeh; Vo, Kiet V.; Shafiei, Mehrzad; Rajiah, Prabhakar; Chalian, Majid
Abstract: Chest computed tomography (CT) is one of the most frequently performed imaging studies. Incidental osseous and articular findings are commonly encountered in chest CTs in daily practice. The spectrum of findings is broad, varying from benign to malignant, and interpretation of these incidental musculoskeletal findings could be challenging for radiologists. In this review, we provide a systematic algorithmic approach for the diagnosis of common articular findings seen on chest CT with recommendations for appropriate follow-up evaluation.